Pengaruh Media Powerpoint Interaktif Terhadap Pemahaman Konsep IPA Materi Cahaya dan Sifatnya Pada Siswa Kelas IV SDN 1 Peresak - Nur Raihani; Lalu Sirajul Hadi; Lalu Wira Zain Amrullah (Mataram University, 2026)
This research is motivated by the science learning process in elementary schools that still uses conventional methods and the use of interactive technology-based learning media has not been optimal. This condition causes fourth grade students of SDN 1 Peresak to have difficulties in understanding abstract science materials, especially in light materials and their properties. Therefore, this study aims to determine the influence of the use of interactive PowerPoint media on light materials and their properties on the understanding of science concepts of grade IV students of SDN 1 Peresak. The research method used is a quantitative approach of the type of pre-experimental design with a One Group Pretest-Posttest Design. The research sample amounted to 23 grade IV students of SDN 1 Peresak who were selected using saturated sampling techniques. Data collection was carried out through multiple-choice objective test instruments (pretest and posttest), observation, and documentation. Data were analyzed using normality tests, homogeneity tests, and hypothesis tests using Paired Sample t-Test analysis. The results of the study showed an increase in students' understanding of concepts with an average score increasing from 40.22 in the pretest to 67.39 in the posttest. The results of the hypothesis test obtained a significance value (Sig. 2-tailed) of 0.000 which is smaller than 0.05 (0.000 < 0.05). Based on the results of the analysis, it can be concluded that the use of interactive PowerPoint media has a positive and significant effect on the understanding of the concept of light matter science and its properties in grade IV students of SDN 1 Peresak.